2018
DOI: 10.1590/1983-21252018v31n418rc
|View full text |Cite
|
Sign up to set email alerts
|

Soil Quality Under Agroforestry Systems and Traditional Agriculture in the Atlantic Forest Biome

Abstract: In the present study, we evaluated the influence of agroforestry systems and traditional agriculture on the physical attributes and biologicals of soil, using as reference a native forest area in Paraty, RJ. Levels of total soil organic carbon, as well as oxidizable fractions and aggregate stability, were analyzed, in addition to the activity and carbon and nitrogen content in the soil microbial biomass, in the 0-5 cm layer, in two distinct seasons (dry and rainy seasons). The agroforestry systems and traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The agroforests in Quilombola communities demonstrate traditional soil management practices and produce food while promoting Atlantic Forest conservation and delivering ecosystem services (Tubenchlak et al, 2021). For example, in Quilombo do Campinho, Tavares et al (2018) found that the agroforestry systems maintained high levels of total organic carbon, as well as providing the same conditions for soil aggregation as the forest. Thus, the authors concluded that the formation of biodiverse agroecosystems by Quilombolas contributed to maintaining soil quality.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…The agroforests in Quilombola communities demonstrate traditional soil management practices and produce food while promoting Atlantic Forest conservation and delivering ecosystem services (Tubenchlak et al, 2021). For example, in Quilombo do Campinho, Tavares et al (2018) found that the agroforestry systems maintained high levels of total organic carbon, as well as providing the same conditions for soil aggregation as the forest. Thus, the authors concluded that the formation of biodiverse agroecosystems by Quilombolas contributed to maintaining soil quality.…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…In Brazil, numerous studies have highlighted the influence of SAFs on soil quality (Maia et al 2006, Mamani-Pati et al 2012, Nigussie & Kissi 2012, Notaro et al 2014, nutrient redistribution in soil profile (Nogueira & Oliveira 2008, Nigussie & Kissi 2012, control of soil, water, and nutrient losses through erosive processes (Aguiar et al 2010, Berhe et al 2014, as well as their role as c and n reservoirs (Maia et al 2007, Simões et al 2010, Ribeiro et al 2019, and their impact on soil structural quality (Silva et al 2011, Tavares et al 2018. These studies indicate that SAFs can serve as important alternatives for soil and water use, management and conservation.…”
Section: Introductionmentioning
confidence: 99%
“…management(Partelli et al 2012;Nogueira et al 2016;Tavares et al 2018). Aragão et al (2020a) also observed higher soil qCO 2 in low production coffee plantations in the Brazilian tropical savanna.…”
mentioning
confidence: 99%